Reviewing Teacher Effectiveness in Improving Student Learning - Iwan Fauzi; Andrian Nuriza Johan (General English Education, 2024)
This research is dealing with the review of teacher effectiveness in improving student learning. A qualitative research method by using technique of library research was applied in analyzing the data in this research. There are four aspects of teacher effectiveness reviewed by the researchers: firstly, the nature of teacher’s effectiveness; secondly, teacher effectiveness based on the teacher’s performance; thirdly, teacher effectiveness based on the student’s achievement; and fourthly, benefits of teacher effectiveness for improving student learning. The results from four aspects which are reviewed give a comprehensive definition of effective teachers and specific method on how to evaluate teacher effectiveness based on teacher performance such as supervisors’ rating, students’ evaluation of teachers, peer-reviewed assessment, and self-evaluation. In addition, the review also evaluated teacher effectiveness based on student’s achievement in which value-added models were exemplified to the measurement of the effectiveness. Last, beyond teachers’ contribution to student achievement; this library research also includes how effective teachers impact student learning which obviously contribute to important outcomes for students as benefits for learning improvement.